PENGARUH KEDISIPLINAN, MOTIVASI, DAN KOMPETENSI GURU TERHADAP KINERJA GURU PADA SMK NUSA DUA TOYA ANYAR - Suandi, I Nyoman (Widyadari: Jurnal Pendidikan, 2018)
The main purpose of this  study were to find out the influence of discipline, motivation and competence to ward?s teacher?s action  in Nusa Dua vocational School. There were three free variables in this study. They were discipline (X1), motivation (X2) and competence (X3). More over, there was  bound  variable called teacher?s action (Y). The score of t score  for disciplene variable in this study was 6.515 with its significanly level was 0.000  more than t table which was  2.042 it showed  that  there was  a H0refusal and Ha acceptance which  means there was a significanly influence of motivation variable to teacher?s action. The score of t score for teacher?s competence(X3) in this study was 7.322 with its significanly level was 0.000 which was more than t table 2.042. it showed that there was a H0 refusal and a Ha acceptance which means there was a significant influence of teacher?s competence variable to ward teacher?s action variable. The calculation of double linier regression pooduced Fscore which was 143.104 and the F table was 3.32. It was a proof that Fscore was more than F table.It showed HO was rejected and Ha was aceptea in significancy level of 0.000 it means there was a significant influence between free variables and bound variable simultanionsly. The competence variable influenced dominantly to wards teachers action in Nusa Dua Toya Anyar Vocational school.The beta score of competence variable was 0.750 which was the most beta score.